PERGULATAN MINORITAS DALAM NEGARA HEGEMONIC: STUDI KASUS MUSLIM BANGSAMORO DI MINDANAO, FILIPINA SELATAN - AHMAD SUAEDY (Jurnal Dialog, 2017)
This article describes the relationship between political entities of the Bangsamoro or Muslims in Mindanao and of the Philippine government which may be said in a nadir since the cancellation of the MoA-AD (Memorandum of Agreement on Ancestral Domain) signing plans between MILF (Mindanao Islamic Liberation Front) and the GRP (Government of the Republic of the Philippines) by the Supreme Court of the country in October 2008. Now their relationship is only bound by the temporary cease-fire. While the actual MILF is the only one course of representation of Muslims in Mindanao in addition to the MNLF (Mindanao National Liberation Front) and Kelompok Datu or traditional leaders. This research deduces that the plurality in the Bangsamoro itself becomes an obstacle in the peace talk process as the absence of a common platform among them. While GRP tends to speak with the faction of it separately, so it was impressed monolithic, there should be efforts to build a joint platform among different groups within the Bangsamoro. Furthermore, the GRP should facilitate the communication and the dialogue among factions within Bangsamoro. Besides, the GRP should convince people in Philippines of how important the peace with Bangsamoro is on behalf of a national interest in a whole.